Melatonin Protects Against Cyclophosphamide-Induced Hepatic and Renal Alterations in Rats (2020)
Cyclophosphamide (CLP), a cytotoxic alkylating agent with immunosuppressive and antitumor properties is used in the treatment of different types of cancers, but it is known to cause toxicity-induced changes to the body tissues. Melatonin, an antioxidant mainly secreted by the pineal gland has protective properties especially against tissue toxicity. This study was aimed at investigating the role of melatonin (MLT) in cyclophosphamide-induced toxicity of the liver and kidney using serum biochemical analysis and histopathology in adult Wistar rats. Twenty-four adult male Wistar rats were grouped into four (n=6): group 1 was injected intraperitoneally with 0.2mL of normal saline for 14 days, group 2 was injected with 10mg/kg of melatonin intraperitoneally for 14 days, group 3 was injected intraperitoneally with 0.2mL of normal saline for 14 days and 150mg/kg of CLP on the 15th day and in group 4, the rats were injected with 10mg/kg of melatonin for 14 days and 150mg/kg of CLP on the 15th day. Forty-eight hours after the last treatment, the rats were weighed; blood samples collected for biochemical analysis while liver and kidney samples were processed for histology. The results revealed that CLP-treated rats had hypokalemia and hypochloremia with a significant increase in the levels of liver and kidney function markers. Histopathological analysis showed congested central vein and widened sinusoids in the liver, while there were widened as well as congested urinary spaces and loop of Henle, with loss of glomerular epithelia in the kidneys. The rats treated with melatonin and CLP showed improvement in body weight, biochemical parameters of hepatic and renal functions as well as improved tissue conditions. In conclusion, a pre-treatment with melatonin is recommended in cyclophosphamide therapy.